Recurrence of pulmonary embolism during anticoagulant treatment: a prospective study. Issue 7 (July 1987) - Girard, P; Mathieu, M; Simonneau, G; Petitpretz, P; Cerrina, J; Herve, P; Rosso, J; Musset, D; Mensch, J; Duroux, P
Abstract : The risk of early recurrence of pulmonary embolism in patients with venous thromboembolic disease treated by anticoagulants is not well established. To determine the risk linked to contemporary proximal deep venous thrombosis, a prospective study was organised to give clinical and scintigraphic surveillance to 50 patients with angiographically proved pulmonary embolism plus phlebographically proved proximal deep vein thrombosis during the first 15 days of anticoagulant treatment. Perfusion lung scans were performed initially and on days 3, 7, and 15. Only two patients had a recurrence of pulmonary embolism during this period; both episodes were revealed by new symptoms, and one recurrence was fatal. The systematic performance of angiography in four patients found to have new scintigraphic defects led to the diagnosis of "spurious scintigraphic recurrence" in three of them. It is concluded that (a) adjusted anticoagulant treatment showed an effectiveness of 96% for preventing early recurrence of pulmonary embolism in this group of supposed high risk patients, and (b) in patients with recent pulmonary embolism new defects on systematic perfusion lung scans are not specific indicators of recurrent pulmonary embolism.